Haematological parameters of adult Pelibuey ewes under humid tropical conditions in Mexico - Rodríguez-Diaz, Diana Laura (2024)
The aim of this study was to evaluate the haematological parameters of adult Pelibuey sheep under conditions of the humid tropics of Mexico. Erythrocytes (RBC, x106/µL), haemoglobin (HB, g/dL), haematocrit (HTO, %), mean corpuscular volume (MCV, fL), mean corpuscular haemoglobin (MCH, pg), and mean corpuscular haemoglobin concentration were analysed. (MCHC, g/dL), leukocyte count (WBC, x103/µL) and platelets (PLT, x103/µL) through descriptive statistics of 86 adult, non-pregnant, non-lactating sheep. The values were: RCB 10.35±1.08 x106/µL; HB 10.83 ±1.53 g/dL, HTO 33.97 ±3.79%, MCV 32.78 ±2.49 fL, MCH 10.63 ±1.16 pg, MCHC 32.55 ±3.35 g/dL, WBC 10.75 ±5.78 x103/µL, PLT 340±658 x103/µL. The haematological parameters obtained are within the average values of the species.